The value of three-dimensional printing modelling for surgical correction of orbital hypertelorism - Engel, Michael; Hoffmann, Jürgen; Castrillón-Oberndorfer, Gregor; Freudlsperger, Christian (Oral and maxillofacial surgery, 2015)
Orbital hypertelorism is defined as an increased distance between both medial and lateral sides of the orbits. Most common causes are frontonasal malformations, craniofacial fissures, encephalocele and a miscellaneous group of various syndromic or chromosomal disorders. Surgical correction of orbital hypertelorism is still challenging. The present report describes a case of severe orbital hypertelorism of an 11-year-old boy, where surgical correction was planned using three-dimensional printing modelling. This approach allowed reducing time of surgery, accurately planning the location of the osteotomies and precontouring the osteosynthesis material. Three-dimensional models are very helpful tools in planning complex craniofacial operative procedures.